Carbon Pricing and Inflation Expectations: Evidence from France - Jannik Hensel; Giacomo Mangiante; Luca Moretti (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines the impact of carbon pricing on firms' inflation expectations and its implications for central banks' price stability mandate. Carbon policy shocks are identified using high-frequency identification and combined with French firm-level survey data. A change in carbon price increases firms' inflation expectations as well as their own expected and realized price growth. The effect on price expectations is more persistent than on actual price growth, resulting in negative forecast errors in the medium-/long-run. We show that a significant portion of the increase in inflation expectations is driven by indirect effects. Firms rely on their own business conditions to form expectations about aggregate price dynamics. Therefore, the expected positive growth in their own prices significantly contributes to the observed increase in inflation expectations. Firms' responses to the shocks vary based on their energy intensity. Low energy-intensive firms are worse forecasters of the impact that the shocks will have on the evolution of their own prices.
Keywords: E31; E52; E58; Q43; Q54; 330; climate policies; carbon pricing; inflation expectations; monetary policy; survey data